Rationale of internationalization of China's national oil companies: seeking natural resources, strategic assets or sectoral specialization? - Lai, Hongyi; O'Hara, Sarah; Wysoczanska, Karolina (Taylor & Francis, 2014)
The bulk of the existing literature emphasized that China's companies sought strategic assets (technology, brands and access to markets) through internationalization in order to overcome latecomers' comparative disadvantage, while some studies suggested that these firms went after natural resources to address China's rising oil imports. The third argument (which we coin the ‘sectoral strength’ hypothesis) suggested that the upstream firms in extractive business would seek natural resources, whereas downstream ones would seek strategic assets. In this study, we examine the rationale of main overseas investment deals (‘going out’) of China's two largest national oil companies during 2002–2010 which were also China's top two non-financial firms with the largest outward investment stocks during 2004–2010. We conclude that these deals can be best explained by the ‘sectoral specialisation’ hypothesis supplemented with a consideration for strategic assets.